2019
DOI: 10.1002/hep4.1363
|View full text |Cite
|
Sign up to set email alerts
|

Selective Liver Estrogen Receptor α Modulation Prevents Steatosis, Diabetes, and Obesity Through the Anorectic Growth Differentiation Factor 15 Hepatokine in Mice

Abstract: Hepatocyte estrogen receptor α (ERα) was recently recognized as a relevant molecular target for nonalcoholic fatty liver disease (NAFLD) prevention. The present study defined to what extent hepatocyte ERα could be involved in preserving metabolic homeostasis in response to a full (17β‐estradiol [E2]) or selective (selective estrogen receptor modulator [SERM]) activation. Ovariectomized mice harboring a hepatocyte‐specific ERα deletion ( LERKO mice) and their wild‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 47 publications
(102 reference statements)
2
27
0
4
Order By: Relevance
“…We found dramatic improvements in phosphorylated AKT (pS473) and FOXO1 (pS256) in male WT mice treated with 17α-E2 ( Figure 5D-E), whereas these benefits were not observed in male ERα KO mice. Our findings are aligned with previous reports demonstrating that hepatic ERα plays a critical role in regulating insulin sensitivity in the liver of male mice [39][40][41]77].…”
Section: α-E2 Improves Liver Disease Pathology In An Erα-dependent supporting
confidence: 92%
See 1 more Smart Citation
“…We found dramatic improvements in phosphorylated AKT (pS473) and FOXO1 (pS256) in male WT mice treated with 17α-E2 ( Figure 5D-E), whereas these benefits were not observed in male ERα KO mice. Our findings are aligned with previous reports demonstrating that hepatic ERα plays a critical role in regulating insulin sensitivity in the liver of male mice [39][40][41]77].…”
Section: α-E2 Improves Liver Disease Pathology In An Erα-dependent supporting
confidence: 92%
“…Furthermore, hepatocyte-specific deletion of ERα was sufficient to abrogate similar estrogen-mediated metabolic benefits [40][41][42]. Given that several reports have linked the administration of 17α-E2 to improvements in metabolic homeostasis, we hypothesized that 17α-E2 signals through ERα to modulate hepatic function and systemic metabolism, thereby potentially contributing to the lifespan-extending effects of 17α-E2.…”
Section: Introductionmentioning
confidence: 97%
“…As alluded to previously, evidence in the literature indicates the binding affinity of 17β-E2 for ERs is dramatically greater than 17α-E2, which has been confirmed with competitive binding assays [32][33][34][35]. In males, very few studies have evaluated the role of ERα in metabolism, although a few recent reports have suggested that ERα plays tissue-specific roles, particularly in the liver, by regulating male metabolic homeostasis [38][39][40][41]55]. These studies, coupled with our current findings, led us to speculate that 17α-E2 may be signaling through ERα in the liver to reverse metabolic disease and potentially extend healthspan and/or lifespan in males.…”
Section: Discussionmentioning
confidence: 53%
“…Other studies have also determined that hepatic steatosis and insulin sensitivity, and therefore the control of gluconeogenesis, are regulated through FOXO1 in an ERα-dependent manner in male mice [39]. Furthermore, liver-specific deletion of ERα was sufficient to abrogate similar estrogen-mediated metabolic benefits [40,41]. Given that several reports have linked the administration of 17α-E2 to improvements in metabolic homeostasis, we hypothesized that 17α-E2 signals through ERα to modulate hepatic function and systemic metabolism, thereby contributing to the lifespan-extending effects of 17α-E2.…”
Section: Introductionmentioning
confidence: 97%
“…The action of the hepatic ERα is particularly relevant when mice are subjected to excess of dietary lipids: with the lack of hepatic ERα, LERKO females result no more protected against the excess of dietary lipids and accumulate lipids in the liver (91), a condition resembling what happens in OVX mice and postmenopausal women (14). However, differently from control OVX females, estrogen treatment fails to prevent lipid deposition in the liver of LERKO females, further stressing the specific relevance of hepatic ERα in the regulation of female hepatic metabolism (287,320).…”
Section: Erα In Femalesmentioning
confidence: 99%